STANDAR BELANJA (ASB) PADA PENYUSUNAN ANGGARAN BELANJA BIMTEK DAN PELATIHAN - Ruth Gok Maria Manalu; Meyzi Heriyanto; Lena Farida (JIANA ( Jurnal Ilmu Administrasi Negara ), 2018)
Abstract: Standard of Shopping (ASB) on Preparation of Bimtek and Training Budget. This study aims to analyze the ASB that can be applied to the preparation of Bimtek Activities and Training budget in SKPD and identify the factors that have not been applied ASB in the preparation of the budget by the Government of Pekanbaru City. The research was conducted by using quantitative and qualitative descriptive research method. The study population is all technical guidance and training activities. Objects studied is the amount of technical guidance and training budget as outlined in DPA SKPD. Technique of collecting secondary data is in the form of document and financial report of government of Pekanbaru City. Technique of simple regression data analysis. The results obtained by ASB model for Bimtek and Training budget are: Y = 16.741.628,67 + 680.493,02 X, Y is total budget, while X is cost driver. There is one activity with an unusual budget value that exceeds the maximum budget limit of Bimtek Package Regulation on Financial Management.